Compact modified rectangular split ring resonator for tri-band satellite applications - Abderraouf Fadhel; Souad Berhab; Rahma Aloulou; Hassene Mnif; Abdennour Belhedri (AIMS Electronics and Electrical Engineering)
This paper contributes to the design of a modified rectangular-shaped metamaterial with a tri-band coverage for reflection and transmission coefficients. Two symmetrical rectangular split ring resonators (SRR) were carefully engineered and then connected by their edges along the axis (Ox) with a substantial C-shaped structure, experiencing the peak surface current value near the magnetic resonances, causing the proposed unit cell to resonate at 5.73 GHz, 8.67 GHz, and 13.78 GHz, where it exhibited negative effective permittivity (ENG), permittivity and permeability (DNG), and permeability (MNG), respectively. A total of 6 × 6 mm2 modified SRR was printed on Rogers RO3006 to achieve a better effective medium ratio (EMR) in the C band (4.55-6.27 GHz), X band (7.81-9.45 GHz), and Ku band (13.15-14.37 GHz), respectively. A comprehensive parametric analysis was performed to illustrate the effect of crucial parameter h on the scattering parameters (S11, S21) of the metamaterial resonant structure (MRSRR) in the specified frequency ranges. Structure underwent additional testing with 1 × 2, 2 × 1, 2 × 2, and 4 × 4 arrays, yielding results that demonstrated sufficient concordance for consideration in the C band [4-8 GHz], X band [8-12 GHz], and Ku band [12-18 GHz] satellite applications. Computer Simulation Technology (CST) Microwave Studio was utilized to reach the scattering parameters and their effective medium characteristics, specifically permittivity and permeability, via the Nicolson–Ross–Weir (NRW) approach, executed through MATLAB code. The surface current was examined, and the corresponding circuit model was confirmed utilizing the Advanced Design System (ADS) software, with results compared against the CST simulation outcomes.